Antibodies to PcpA and PhtD protect mice against Streptococcus pneumoniae by a macrophage- and complement-dependent mechanism - Lucian Visan; Nicolas Rouleau; Emilie Proust; Loïc Peyrot; Arnaud Donadieu; Martina Ochs (Taylor & Francis Group, 2018)
Currently marketed Streptococcus pneumoniae (Spn) vaccines, which contain polysaccharide capsular antigens from the most common Spn serotypes, have substantially reduced pneumococcal disease rates but have limited coverage. A trivalent pneumococcal protein vaccine containing pneumococcal choline-binding protein A (PcpA), pneumococcal histidine triad protein D (PhtD), and detoxified pneumolysin is being developed to provide broader, cross-serotype protection. Antibodies against detoxified pneumolysin protect against bacterial pneumonia by neutralizing Spn-produced pneumolysin, but how anti-PhtD and anti-PcpA antibodies protect against Spn has not been established. Here, we used a murine passive protection sepsis model to investigate the mechanism of protection by anti-PhtD and anti-PcpA antibodies. Depleting complement using cobra venom factor eliminated protection by anti-PhtD and anti-PcpA monoclonal antibodies (mAbs). Consistent with a requirement for complement, complement C3 deposition on Spn in vitro was enhanced by anti-PhtD and anti-PcpA mAbs and by sera from PhtD- and PcpA-immunized rabbits and humans. Moreover, in the presence of complement, anti-PhtD and anti-PcpA mAbs increased uptake of Spn by human granulocytes. Depleting neutrophils using anti-Ly6G mAbs, splenectomy, or a combination of both did not affect passive protection against Spn, whereas depleting macrophages using clodronate liposomes eliminated protection. These results suggest anti-PhtD and anti-PcpA antibodies induced by pneumococcal protein vaccines protect against Spn by a complement- and macrophage-dependent opsonophagocytosis.